A surface selectively metallized ceramic and its preparation method and application

By accurately covering and pretreating the surface of the ceramic substrate and combining electroless plating technology, surface selective metallized ceramics are formed, which solves the problem of lack of regional selectivity and damage to the ceramic substrate in the prior art, and achieves excellent binding force and density between the ceramic substrate and the copper metal layer.

CN117843400BActive Publication Date: 2025-04-04HANGZHOU WIN WIN TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202410017726.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-05
Publication Date
2025-04-04
Estimated Expiration
2044-01-05

AI Technical Summary

Technical Problem

The existing ceramic metallization technology has problems such as the lack of regional selectivity of the copper metal layer, the pretreatment process causes damage to the mechanical properties and microstructure of the ceramic substrate, the raw materials used have great harm to the human environment, and the electroplating process cannot ensure current uniformity and the uniform stability of the copper metal layer.

Method used

The 3D printing ink is used to accurately cover the parts of the ceramic substrate that do not need metallization on the surface. By removing grease and hydroxylation with surface, the formation of self-assembled single-molecular layer and its densification and activation treatment, the final electroless plating is carried out in the electroless copper plating solution to form surface selective metallized ceramics.

Benefits of technology

The excellent bonding force and density of the copper metal layer on the surface of the ceramic substrate are achieved, the microstructure of the copper metal layer is uniform, and the process is simple and easy to operate, green and environmentally friendly, and low cost.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a surface selectively metallized ceramic, which is prepared by the following steps: (1) covering the surface of a ceramic substrate; (2) pretreatment of the uncovered portion of the surface of the ceramic substrate: removing grease and surface hydroxylation, forming a self-assembled monolayer and its densification, and activation; (3) metallizing the uncovered portion of the surface of the ceramic substrate; (4) removing the 3D printing ink covering layer. The preparation method of the surface selectively metallized ceramic of the present invention is simple and easy to operate, the process is green and environmentally friendly, and the cost is low. The copper metal layer on the surface of the ceramic prepared by the present invention has excellent bonding strength with the ceramic substrate, the copper metal layer has good density, and the microstructure of the copper metal layer is uniform. The surface selectively metallized ceramic of the present invention and the preparation method thereof can provide a reference for a new generation of semiconductor manufacturing technology, which is of great significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic packaging, and in particular to a surface selectively metallized ceramic and a preparation method and application thereof. Background Art

[0002] With the advent of the information age, semiconductor chips are mainly developing in the direction of high integration, multifunctionality, high power and miniaturization, but the heat dissipation problem is becoming increasingly severe. Therefore, the development of packaging materials with excellent thermal diffusion performance has become one of the hot spots in the current electronic packaging material field. Ceramics are often used as packaging substrates in electronic packaging structures because they have high thermal conductivity, low dielectric constant, electrical insulation, excellent mechanical properties and a thermal expansion coefficient similar to that of chip materials.

[0003] Ceramic substrates mainly include ceramic substrates and metal circuit layers, and the excellent bonding between the ceramic substrate and the metal circuit layer is an important guarantee for the quality of later packaging. Due to the large difference in thermal expansion coefficients between ceramics and metals, in order to ensure high-quality connection between the ceramic substrate and the metal circuit layer, a layer of metal film must be formed on the surface of the ceramic substrate. This process is ceramic metallization. At present, the main methods of ceramic metallization include sintering, magnetron sputtering, vacuum evaporation coating, vapor deposition (CVD, PVD) and chemical plating. Since the ceramic surface does not have catalytic activity, it is often necessary to pre-treat it when using chemical plating to form active points on the ceramic surface. The success of pretreatment is often determined by the main performance indicators of ceramic metallization-selective coverage and bonding.

[0004] Chinese patent CN114990533A (publication date 2022.09.02) discloses a method for improving the bonding force of electroplated copper on the surface of a ceramic substrate, which optimizes the etching roughening process parameters before ceramic chemical plating, and combines the electroplating process to replace the magnetron sputtering thin film method to finally obtain ceramic surface metallization. The advantage of this method is that the prepared ceramic substrate has excellent bonding force with the copper metal layer, and there is no blistering and peeling phenomenon even when baked in a high temperature environment, and the thickness and uniformity of the copper metal layer are effectively guaranteed; the disadvantages of this method are: 1) The prepared copper metal layer does not have regional selectivity, 2) Although the etching process of the pretreatment process effectively improves the bonding force, it will also cause certain harm to the mechanical properties and microstructure of the ceramic substrate, 3) The raw materials used, such as formaldehyde and metallic sodium, will cause great harm to humans and the environment, 4) The electroplating therein cannot guarantee or is extremely difficult to guarantee the uniformity of the current, and it is also impossible to guarantee whether the later electroplating will affect the stability of the uniformity of the copper metal layer.

[0005] Chinese patent CN114163259A (publication date 2022.03.11) discloses a method for metallizing a ceramic surface and a metallized ceramic, which first forms a circuit pattern area by laser irradiating a ceramic substrate, then chemically copper-plating the irradiated area, and finally brazing and etching in sequence to form a ceramic substrate. The advantage of this method is that the thickness of the copper metal layer on the formed ceramic substrate can be guaranteed while also having regional selectivity and excellent bonding strength; the disadvantages of this method are: 1) the raw materials used, such as formaldehyde and hydrofluoric acid, will cause great harm to humans and the environment, 2) the etching in the subsequent processing process will cause irreparable damage to the microstructure and mechanical properties of the ceramic substrate, 3) the use of laser equipment and ultraviolet radiation equipment in the process is extremely expensive and the resulting process is complex. Summary of the invention

[0006] The purpose of the present invention is to provide a surface selectively metallized ceramic and a preparation method and application thereof, so as to solve the deficiencies of the prior art.

[0007] The present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a surface selectively metallized ceramic, wherein the surface selectively metallized ceramic is prepared by the following steps:

[0009] (1) Ceramic substrate surface coverage: Using 3D printing ink to accurately cover the part of the ceramic substrate surface that does not require metallization, and then let it dry naturally for later use;

[0010] (2) Pretreatment of the uncovered portion of the ceramic substrate surface: The ceramic substrate obtained in step (1) is pretreated, and the specific operation is as follows:

[0011] (a) Degreasing and surface hydroxylation: The ceramic substrate obtained in step (1) is immersed in a degreasing solution to remove substances including oxides and grease on the surface of the ceramic substrate, and a hydroxyl layer is formed on the surface of the ceramic substrate, and then the ceramic substrate is taken out and washed with water;

[0012] (b) Formation of a self-assembled monolayer and its densification: immersing the ceramic substrate obtained in step (a) in an ethanol solution containing a grafting agent to obtain a self-assembled monolayer on the ceramic substrate, then taking it out, washing it with water and drying it, and then baking it in an inert gas to densify the self-assembled monolayer;

[0013] (c) Activation: The ceramic substrate with the self-assembled monolayer obtained in step (b) is immersed in a 2+ The activation solution is used to capture Ni 2+ After taking it out, immerse it in a reducing solvent to capture Ni 2+ It is reduced to Ni, and then taken out and washed for use; among them, Ni2+ Provided by one or more of nickel acetate, nickel sulfate, nickel sulfamate, and basic nickel carbonate;

[0014] (3) Metallizing the uncovered portion of the surface of the ceramic substrate: immersing the ceramic substrate obtained in step (2) in a chemical copper plating solution for chemical plating, so that the surface is covered with a copper metal layer to achieve the purpose of metallization, and then taking it out for washing;

[0015] (4) Removing the 3D printing ink covering layer: Immersing the ceramic obtained in step (3) in an ethanol solution to dissolve the 3D printing ink covering layer, then taking it out, washing it with water and air-drying it, thereby obtaining a surface selectively metallized ceramic.

[0016] Furthermore, the ceramic substrate in step (1) includes an Al2O3 ceramic substrate, a BeO ceramic substrate or an AlN ceramic substrate.

[0017] Furthermore, the degreasing solution in step (2) a specifically comprises 30-40 g / l ammonia water, 25-35 g / l Na2CO3, 15-30 g / l NaHCO3, 25-40 g / l NaH2PO4, 5-8 g / l Tween-60, 25-35 g / l Na2SiO3, 10-15 g / l H2O2, 0.3-0.8 g / l N-acetoacetanilide and deionized water, and its working temperature is 65-70° C., the working time is 5-10 min, and during the working process, the pH is maintained at 7.5-8 with ammonia water;

[0018] The ethanol solution containing the grafting agent in step (2) b is an ethanol solution containing 10-25 g / l of silane coupling agent KH-550, and its working temperature is 25-30° C., and the working time is 15-25 min; the drying temperature is 45-65° C., and the drying time is 5-10 min; the inert gas is N2 or Ar, the baking temperature is 55-65° C., and the baking time is 30-45 min;

[0019] Step (2)c contains Ni 2+ The specific composition of the activation solution is 15-25g / l Ni 2+ , 5-10g / l glycolic acid, 15-20g / l malic acid, 10-25g / l lactic acid and deionized water, the working temperature is 25-35°C, and the working time is 5-20min; the specific components of the reducing solvent are 15-25g / l potassium borohydride and deionized water, the working temperature is 65-70°C, and the working time is 5-8min.

[0020] Furthermore, the chemical copper plating solution in step (3) specifically comprises 5 to 8 g / l Cu 2+, 1-3 g / l aminosulfonic acid, 2-5 g / l aspartic acid, 15-25 g / l ethylenediaminetetraacetic acid, 10-25 g / l tartaric acid, 15-30 g / l reducing agent, 3-8 ppm surfactant, 2-5 ml / l ethylene glycol, 5-10 ppm stabilizer; wherein, Cu 2+ The invention is provided by one or more of copper acetate, copper sulfate and copper oxalate, the reducing agent is one or two of glyoxylic acid and potassium borohydride, the surfactant is one or more of hexadecyltrimethylammonium bromide, dioctyl sodium succinate and taurine, the stabilizer is one or more of isothiourea propanesulfonic acid inner salt, urea, stannous sulfate, malic acid and S-carboxyethyl isothiourea humid salt, and the solvent is deionized water; the working temperature is 85-90°C, the working time is 85-90 minutes, and during the working process, 50v / v% ammonia water and 20wt% H2SO4 are used to keep the pH value at 8.5-9, and the 50% ammonia water is obtained by mixing ammonia water and deionized water in a volume ratio of 1:1.

[0021] Furthermore, the ethanol solution in step (4) is a 30-45 v / v % ethanol solution, the working temperature is 20-30° C., and the working time is 10-25 min.

[0022] The second aspect of the present invention provides a method for preparing a surface selectively metallized ceramic, which is prepared by the following steps:

[0023] (1) Ceramic substrate surface coverage: Using 3D printing ink to accurately cover the part of the ceramic substrate surface that does not require metallization, and then let it dry naturally for later use;

[0024] (2) Pretreatment of the uncovered portion of the ceramic substrate surface: The ceramic substrate obtained in step (1) is pretreated, and the specific operation is as follows:

[0025] (a) Degreasing and surface hydroxylation: The ceramic substrate obtained in step (1) is immersed in a degreasing solution to remove substances including oxides and grease on the surface of the ceramic substrate, and a hydroxyl layer is formed on the surface of the ceramic substrate, and then the ceramic substrate is taken out and washed with water;

[0026] (b) Formation of a self-assembled monolayer and its densification: immersing the ceramic substrate obtained in step (a) in an ethanol solution containing a grafting agent to obtain a self-assembled monolayer on the ceramic substrate, then taking it out, washing it with water and drying it, and then baking it in an inert gas to densify the self-assembled monolayer;

[0027] (c) Activation: The ceramic substrate with the self-assembled monolayer obtained in step (b) is immersed in a 2+ The activation solution is used to capture Ni 2+ After taking it out, immerse it in a reducing solvent to capture Ni 2+It is reduced to Ni, and then taken out and washed for use; among them, Ni 2+ Provided by one or more of nickel acetate, nickel sulfate, nickel sulfamate, and basic nickel carbonate;

[0028] (3) Metallizing the uncovered portion of the surface of the ceramic substrate: immersing the ceramic substrate obtained in step (2) in a chemical copper plating solution for chemical plating, so that the surface is covered with a copper metal layer to achieve the purpose of metallization, and then taking it out for washing;

[0029] (4) Removing the 3D printing ink covering layer: Immersing the ceramic obtained in step (3) in an ethanol solution to dissolve the 3D printing ink covering layer, then taking it out, washing it with water and air-drying it, thereby obtaining a surface selectively metallized ceramic.

[0030] Furthermore, the ceramic substrate in step (1) includes an Al2O3 ceramic substrate, a BeO ceramic substrate or an AlN ceramic substrate.

[0031] Furthermore, the degreasing solution in step (2) a specifically comprises 30-40 g / l ammonia water, 25-35 g / l Na2CO3, 15-30 g / l NaHCO3, 25-40 g / l NaH2PO4, 5-8 g / l Tween-60, 25-35 g / l Na2SiO3, 10-15 g / l H2O2, 0.3-0.8 g / l N-acetoacetanilide and deionized water, and its working temperature is 65-70° C., the working time is 5-10 min, and during the working process, the pH is maintained at 7.5-8 with ammonia water;

[0032] The ethanol solution containing the grafting agent in step (2) b is an ethanol solution containing 10-25 g / l of silane coupling agent KH-550, and its working temperature is 25-30° C., and the working time is 15-25 min; the drying temperature is 45-65° C., and the drying time is 5-10 min; the inert gas is N2 or Ar, the baking temperature is 55-65° C., and the baking time is 30-45 min;

[0033] Step (2)c contains Ni 2+ The specific composition of the activation solution is 15-25g / l Ni 2+ , 5-10g / l glycolic acid, 15-20g / l malic acid, 10-25g / l lactic acid and deionized water, the working temperature is 25-35°C, and the working time is 5-20min; the specific components of the reducing solvent are 15-25g / l potassium borohydride and deionized water, the working temperature is 65-70°C, and the working time is 5-8min.

[0034] Furthermore, the chemical copper plating solution in step (3) specifically comprises 5 to 8 g / l Cu 2+, 1-3 g / l aminosulfonic acid, 2-5 g / l aspartic acid, 15-25 g / l ethylenediaminetetraacetic acid, 10-25 g / l tartaric acid, 15-30 g / l reducing agent, 3-8 ppm surfactant, 2-5 ml / l ethylene glycol, 5-10 ppm stabilizer; wherein, Cu 2+ The invention is provided by one or more of copper acetate, copper sulfate and copper oxalate, the reducing agent is one or two of glyoxylic acid and potassium borohydride, the surfactant is one or more of hexadecyltrimethylammonium bromide, dioctyl sodium succinate and taurine, the stabilizer is one or more of isothiourea propanesulfonic acid inner salt, urea, stannous sulfate, malic acid and S-carboxyethyl isothiourea humid salt, and the solvent is deionized water; the working temperature is 85-90°C, the working time is 85-90 minutes, and during the working process, 50v / v% ammonia water and 20wt% H2SO4 are used to keep the pH value at 8.5-9, and the 50% ammonia water is obtained by mixing ammonia water and deionized water in a volume ratio of 1:1.

[0035] Furthermore, the ethanol solution in step (4) is a 30-45 v / v % ethanol solution, the working temperature is 20-30° C., and the working time is 10-25 min.

[0036] The third aspect of the present invention provides the use of the above-mentioned surface selectively metallized ceramic in electronic packaging.

[0037] Beneficial effects of the present invention:

[0038] 1. The preparation method of the surface selectively metallized ceramic of the present invention is simple and easy to operate, the process is green and environmentally friendly, and the cost is low. The copper metal layer on the surface of the ceramic prepared by the present invention has excellent bonding strength with the ceramic substrate, the copper metal layer has good density, and the microstructure in the copper metal layer is uniform. The surface selectively metallized ceramic of the present invention and the preparation method thereof can provide a reference for a new generation of semiconductor manufacturing technology, which is of great significance.

[0039] 2. The method for preparing surface selectively metallized ceramics of the present invention further effectively improves the bonding force between the copper metal layer and the ceramic substrate and the density of the copper metal layer by forming a self-assembled monolayer on the surface of the ceramic substrate and densifying the self-assembled monolayer.

[0040] 3. The preparation method of the surface selectively metallized ceramic of the present invention is to cooperate with aspartic acid and aminosulfonic acid, and the former can carry Cu 2+ It can migrate to the ceramic substrate faster, and the latter can effectively 2+ A "bridge"-like structure is formed between the two layers, which ensures that the chemical copper plating solution can generate a copper metal layer at a faster and more stable plating speed, so that the thickness of the copper metal layer (generally 30 to 50 μm) is effectively guaranteed. DETAILED DESCRIPTION

[0041] The present invention is further explained below in conjunction with the examples. The following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0042] The ammonia water mentioned below refers to industrial ammonia water, which is an aqueous solution containing 25% to 28% ammonia.

[0043] The crystal water contained in the following compounds is not included in the mass.

[0044] A surface selectively metallized ceramic, wherein the surface selectively metallized ceramic is prepared by the following steps:

[0045] (1) Ceramic substrate surface covering: using 3D printing ink to accurately cover the part of the ceramic substrate surface that does not need to be metallized, and naturally drying it for later use; the ceramic substrate includes an Al2O3 ceramic substrate, a BeO ceramic substrate or an AlN ceramic substrate;

[0046] (2) Pretreatment of the uncovered portion of the ceramic substrate surface: The ceramic substrate obtained in step (1) is pretreated, and the specific operation is as follows:

[0047] (a) Removing grease and surface hydroxylation: immersing the ceramic substrate obtained in step (1) in a degreasing solution at 65-70° C. for 5-10 minutes, during which the pH value of the degreasing solution is maintained at 7.5-8 with aqueous ammonia, so as to remove substances including oxides and grease on the surface of the ceramic substrate and form a hydroxyl layer on the surface, and then taking out and washing with water; wherein the degreasing solution specifically comprises 30-40 g / l aqueous ammonia, 25-35 g / l Na2CO3, 15-30 g / l NaHCO3, 25-40 g / l NaH2PO4, 5-8 g / l Tween-60, 25-35 g / l Na2SiO3, 10-15 g / l H2O2, 0.3-0.8 g / l N-acetoacetanilide and deionized water;

[0048] (b) Formation of a self-assembled monolayer and its densification: the ceramic substrate obtained in step (a) is immersed in an ethanol solution containing a grafting agent at 25 to 30° C. for 15 to 25 minutes to obtain a self-assembled monolayer on the ceramic substrate, then taken out, washed with water and dried at 45 to 65° C. for 5 to 10 minutes, and then placed in an inert gas and baked at 55 to 65° C. for 30 to 45 minutes to densify the self-assembled monolayer; wherein the ethanol solution containing the grafting agent is an ethanol solution containing 10 to 25 g / l of silane coupling agent KH-550; the inert gas is N2 or Ar;

[0049] (c) Activation: First, immerse the ceramic substrate with the self-assembled monolayer obtained in step (b) in a 25-35°C Ni-containing 2+ The Ni 2+ After taking it out, immerse it in a reducing solvent at 65-70℃ for 5-8min to capture Ni 2+ It is reduced to Ni, and then taken out and washed for use; among them, Ni 2+ The specific composition of the activation solution is 15-25g / l Ni 2+ , 5-10 g / l glycolic acid, 15-20 g / l malic acid, 10-25 g / l lactic acid and deionized water, Ni 2+ It is provided by one or more of nickel acetate, nickel sulfate, nickel sulfamate, and basic nickel carbonate; the specific components of the reducing solvent are 15-25g / l potassium borohydride and deionized water;

[0050] (3) Metallization of the uncovered portion of the ceramic substrate surface: The ceramic substrate obtained in step (2) is immersed in an 85-90° C. chemical copper plating solution for 85-90 min, during which the pH of the chemical copper plating solution is maintained at 8.5-9 using 50 v / v% ammonia water and 20 wt% H2SO4, so that the surface is covered with a copper metal layer (generally with a thickness of 30-50 μm) to achieve the goal of metallization, and then taken out for washing; wherein the chemical copper plating solution specifically comprises 5-8 g / l Cu 2+ , 1-3 g / l aminosulfonic acid, 2-5 g / l aspartic acid, 15-25 g / l ethylenediaminetetraacetic acid, 10-25 g / l tartaric acid, 15-30 g / l reducing agent, 3-8 ppm surfactant, 2-5 ml / l ethylene glycol, 5-10 ppm stabilizer; Cu 2+ It is provided by one or more of copper acetate, copper sulfate, and copper oxalate; the reducing agent is one or two of glyoxylic acid and potassium borohydride; the surfactant is one or more of hexadecyltrimethylammonium bromide, dioctyl sodium sulfosuccinate, and taurine; the stabilizer is one or more of isothiourea propanesulfonic acid inner salt, urea, stannous sulfate, malic acid, and S-carboxyethyl isothiourea humid salt; the solvent is deionized water; 50% ammonia water is obtained by mixing ammonia water and deionized water in a volume ratio of 1:1;

[0051] (4) Removing the 3D printing ink covering layer: immersing the ceramic obtained in step (3) in an ethanol solution at 20 to 30° C. for 10 to 25 minutes to dissolve the 3D printing ink covering layer, then taking it out, washing it with water and air-drying it to obtain a surface selectively metallized ceramic; wherein the ethanol solution is a 30 to 45 v / v % ethanol solution.

[0052] A method for preparing a surface selectively metallized ceramic is prepared by the following steps:

[0053] (1) Ceramic substrate surface covering: using 3D printing ink to accurately cover the part of the ceramic substrate surface that does not need to be metallized, and naturally drying it for later use; the ceramic substrate includes an Al2O3 ceramic substrate, a BeO ceramic substrate or an AlN ceramic substrate;

[0054] (2) Pretreatment of the uncovered portion of the ceramic substrate surface: The ceramic substrate obtained in step (1) is pretreated, and the specific operation is as follows:

[0055] (a) Removing grease and surface hydroxylation: immersing the ceramic substrate obtained in step (1) in a degreasing solution at 65-70° C. for 5-10 minutes, during which the pH value of the degreasing solution is maintained at 7.5-8 with aqueous ammonia, so as to remove substances including oxides and grease on the surface of the ceramic substrate and form a hydroxyl layer on the surface, and then taking out and washing with water; wherein the degreasing solution specifically comprises 30-40 g / l aqueous ammonia, 25-35 g / l Na2CO3, 15-30 g / l NaHCO3, 25-40 g / l NaH2PO4, 5-8 g / l Tween-60, 25-35 g / l Na2SiO3, 10-15 g / l H2O2, 0.3-0.8 g / l N-acetoacetanilide and deionized water;

[0056] (b) Formation of a self-assembled monolayer and its densification: the ceramic substrate obtained in step (a) is immersed in an ethanol solution containing a grafting agent at 25 to 30° C. for 15 to 25 minutes to obtain a self-assembled monolayer on the ceramic substrate, then taken out, washed with water and dried at 45 to 65° C. for 5 to 10 minutes, and then placed in an inert gas and baked at 55 to 65° C. for 30 to 45 minutes to densify the self-assembled monolayer; wherein the ethanol solution containing the grafting agent is an ethanol solution containing 10 to 25 g / l of silane coupling agent KH-550; the inert gas is N2 or Ar;

[0057] (c) Activation: First, immerse the ceramic substrate with the self-assembled monolayer obtained in step (b) in a 25-35°C Ni-containing 2+ The Ni 2+ After taking it out, immerse it in a reducing solvent at 65-70℃ for 5-8min to capture Ni 2+ It is reduced to Ni, and then taken out and washed for use; among them, Ni 2+ The specific composition of the activation solution is 15-25g / l Ni 2+ , 5-10 g / l glycolic acid, 15-20 g / l malic acid, 10-25 g / l lactic acid and deionized water, Ni 2+It is provided by one or more of nickel acetate, nickel sulfate, nickel sulfamate, and basic nickel carbonate; the specific components of the reducing solvent are 15-25g / l potassium borohydride and deionized water;

[0058] (3) Metallization of the uncovered portion of the ceramic substrate surface: The ceramic substrate obtained in step (2) is immersed in an 85-90° C. chemical copper plating solution for 85-90 min, during which the pH of the chemical copper plating solution is maintained at 8.5-9 using 50 v / v% ammonia water and 20 wt% H2SO4, so that the surface is covered with a copper metal layer (generally with a thickness of 30-50 μm) to achieve the goal of metallization, and then taken out for washing; wherein the chemical copper plating solution specifically comprises 5-8 g / l Cu 2+ , 1-3 g / l aminosulfonic acid, 2-5 g / l aspartic acid, 15-25 g / l ethylenediaminetetraacetic acid, 10-25 g / l tartaric acid, 15-30 g / l reducing agent, 3-8 ppm surfactant, 2-5 ml / l ethylene glycol, 5-10 ppm stabilizer; Cu 2+ It is provided by one or more of copper acetate, copper sulfate, and copper oxalate; the reducing agent is one or two of glyoxylic acid and potassium borohydride; the surfactant is one or more of hexadecyltrimethylammonium bromide, dioctyl sodium sulfosuccinate, and taurine; the stabilizer is one or more of isothiourea propanesulfonic acid inner salt, urea, stannous sulfate, malic acid, and S-carboxyethyl isothiourea humid salt; the solvent is deionized water; 50% ammonia water is obtained by mixing ammonia water and deionized water in a volume ratio of 1:1;

[0059] (4) Removing the 3D printing ink covering layer: immersing the ceramic obtained in step (3) in an ethanol solution at 20 to 30° C. for 10 to 25 minutes to dissolve the 3D printing ink covering layer, then taking it out, washing it with water and air-drying it to obtain a surface selectively metallized ceramic; wherein the ethanol solution is a 30 to 45 v / v % ethanol solution.

[0060] The above-mentioned surface selectively metallized ceramics are used in electronic packaging.

[0061] The adhesion of the parts in the following embodiments was tested by referring to the 2.8 cross-cut test and 2.12 thermal shock test in GBT5270-2005 "Review of Test Methods for Adhesion Strength of Electrodeposited and Chemically Deposited Metal Coatings on Metal Substrates". The density of the coating was checked by a crystal phase microscope - that is, the parts were cut longitudinally and samples were prepared, and then a crystal phase microscope was used to check whether there were gaps between the copper metal layer and the ceramic substrate and whether there were holes in the copper metal layer. The microstructure of the copper metal layer was checked by a scanning electron microscope.

[0062] The degreasing solution in the following examples specifically comprises 40 g / l ammonia water, 32 g / l Na2CO3, 20 g / l NaHCO3, 25 g / l NaH2PO4, 8 g / l Tween-60, 30 g / l Na2SiO3, 12 g / l H2O2, 0.5 g / l N-acetoacetanilide and deionized water. During the working process, ammonia water is used to maintain the pH at 7.5; Ni 2+ The specific composition of the activation solution is 20g / l Ni 2+ (Ni 2+ provided by nickel sulfate), 8g / l glycolic acid, 15g / l malic acid, 12g / l lactic acid and deionized water; the specific components of the reducing solvent are 22g / l potassium borohydride and deionized water.

[0063] Example 1

[0064] The specific composition of the chemical copper plating solution in this embodiment is 6g / l Cu 2+ (Cu 2+ The mixture was prepared by mixing 2.5 g / l sulfamic acid, 3 g / l aspartic acid, 20 g / l ethylenediaminetetraacetic acid, 15 g / l tartaric acid, 30 g / l glyoxylic acid, 5 ppm sodium dioctyl succinate sulfonate, 3 ml / l ethylene glycol, 3 ppm S-carboxyethyl isothiourea salt, 2 ppm urea and deionized water. During the working process, the pH was maintained at 8.5 with 50 v / v% ammonia water and 20 wt% H2SO4.

[0065] 1. Take 4 AlN ceramic blocks with a size of 3000mm*5000mm*2mm, accurately cover the parts of the AlN ceramic blocks that do not need to be metallized with 3D printing ink, and dry them naturally for later use;

[0066] 2. Immerse the AlN ceramic block from step 1 in a 65°C degreasing solution for 8 minutes, then take it out and wash it with water;

[0067] 3. Immerse the AlN ceramic block from step 2 in an ethanol solution containing 15 g / l KH-550 at 25°C for 15 min, then take it out, wash it with water, dry it at 60°C for 10 min, and then bake it at 55°C in a tube furnace filled with N2 for 30 min;

[0068] 4. Immerse the AlN ceramic blocks from step 3 in 30°C Ni-containing 2+ The mixture was placed in the activation solution for 5 minutes, and in the reducing solvent at 65°C for 6 minutes, and then washed with water for later use;

[0069] 5. Immerse the AlN ceramic block in step 4 into an 85°C chemical copper plating solution for 85 minutes, then take it out and wash it with water;

[0070] 6. Immerse the AlN ceramic block obtained in step 5 in a 40 v / v% ethanol solution at 25° C. for 10 min to dissolve the 3D printing ink covering layer, then take it out, wash it with water and air-dry it to obtain a metallized AlN ceramic block.

[0071] The metallized AlN ceramic block prepared in this embodiment showed no abnormal phenomena such as bubbling and peeling between the copper metal layer and the AlN ceramic block after a 250°C thermal shock test, and no peeling of the copper metal layer occurred in a cross-cutting test; no voids or holes were found between the copper metal layer and the AlN ceramic block or the copper metal layer in observation under a crystal phase microscope; and the scanning electron microscope showed that the microstructure of the copper metal layer was uniform and had no abnormalities.

[0072] Example 2

[0073] The specific composition of the chemical copper plating solution in this embodiment is 5g / l Cu 2+ (Cu 2+ Provided by copper oxalate), 2g / l sulfamic acid, 5g / l aspartic acid, 23g / l ethylenediaminetetraacetic acid, 10g / l tartaric acid, 25g / l glyoxylic acid, 6ppm hexadecyltrimethylammonium bromide, 5ml / l ethylene glycol, 3ppm S-carboxyethyl isothiourea humid salt, 2ppm isothiourea propanesulfonic acid inner salt and deionized water. During the working process, 50v / v% ammonia water and 20wt% H2SO4 were used to maintain the pH at 8.5.

[0074] 1. Take 2 Al2O3 ceramic blocks with a size of 3500mm*5000mm*5mm, accurately cover the parts of the Al2O3 ceramic blocks that do not need to be metallized with 3D printing ink, and dry them naturally for later use;

[0075] 2. Immerse the Al2O3 ceramic block from step 1 in a 70°C degreasing solution for 10 minutes, then take it out and wash it with water;

[0076] 3. The Al2O3 ceramic block of step 2 was immersed in an ethanol solution containing 20 g / l KH-550 at 30°C for 20 min, then taken out, washed with water and dried at 60°C for 10 min, and then placed in a tubular furnace filled with Ar and baked at 65°C for 40 min;

[0077] 4. Immerse the Al2O3 ceramic blocks from step 3 in 30°C Ni-containing 2+ The mixture was placed in the activation solution for 10 min, and in the reducing solvent at 65°C for 6 min, and then washed with water for later use;

[0078] 5. Immerse the Al2O3 ceramic block in step 4 into a 90°C chemical copper plating solution for 85 minutes, then take it out and wash it with water;

[0079] 6. The Al2O3 ceramic block obtained in step 5 is immersed in a 40 v / v% ethanol solution at 25°C for 20 min to dissolve the 3D printing ink covering layer, and then taken out, washed with water and air-dried to obtain a metallized Al2O3 ceramic block.

[0080] The metallized Al2O3 ceramic block prepared in this embodiment showed no abnormal phenomena such as bubbling and peeling between the copper metal layer and the Al2O3 ceramic block after a 250°C thermal shock test, and no peeling of the copper metal layer occurred in a cross-cutting test; in observation under a crystal phase microscope, no voids or holes were found between the copper metal layer and the Al2O3 ceramic block or the copper metal layer; and in a scanning electron microscope, it can be observed that the microstructure of the copper metal layer is uniform and has no abnormalities.

Claims

1. A surface selectively metallized ceramic, characterized in that: The surface selectively metallized ceramic is prepared by the following steps: (1) Ceramic substrate surface coverage: Using 3D printing ink to accurately cover the parts of the ceramic substrate surface that do not require metallization, and then let them dry naturally for later use; (2) Pretreatment of the uncovered portion of the ceramic substrate surface: The ceramic substrate obtained in step (1) is pretreated, and the specific operation is as follows: (a) Degreasing and surface hydroxylation: immersing the ceramic substrate obtained in step (1) in a degreasing solution to remove substances including oxides and grease on the surface of the ceramic substrate and forming a hydroxyl layer on the surface, and then taking it out for washing; wherein the degreasing solution specifically comprises 30-40 g / l ammonia water, 25-35 g / l Na2CO3, 15-30 g / l NaHCO3, 25-40 g / l NaH2PO4, 5-8 g / l Tween-60, 25-35 g / l Na2SiO3, 10-15 g / l H2O2, 0.3-0.8 g / l N-acetoacetanilide and deionized water, and the working temperature is 65-70°C, the working time is 5-10 min, and the pH is maintained at 7.5-8 during the working process; (b) Formation of a self-assembled monolayer and its densification: immersing the ceramic substrate obtained in step (a) in an ethanol solution containing a grafting agent to obtain a self-assembled monolayer on the ceramic substrate, then taking it out, washing it with water and drying it, and then baking it in an inert gas to densify the self-assembled monolayer; wherein the ethanol solution containing the grafting agent is an ethanol solution containing 10 to 25 g / l of silane coupling agent KH-550, its working temperature is 25 to 30°C, and the working time is 15 to 25 min; the drying temperature is 45 to 65°C, and the drying time is 5 to 10 min; the inert gas is N2 or Ar, the baking temperature is 55 to 65°C, and the baking time is 30 to 45 min; (c) Activation: The ceramic substrate with the self-assembled monolayer obtained in step (b) is immersed in a 2+ The activation solution is used to capture Ni 2+ After taking it out, immerse it in a reducing solvent to capture Ni 2+ It is reduced to Ni, and then taken out and washed for use; among them, Ni 2+ Provided by one or more of nickel acetate, nickel sulfate, nickel sulfamate, and basic nickel carbonate; containing Ni 2+ The specific composition of the activation solution is 15-25g / l Ni 2+ , 5-10g / l glycolic acid, 15-20g / l malic acid, 10-25g / l lactic acid and deionized water, the working temperature is 25-35°C, and the working time is 5-20min; the specific components of the reducing solvent are 15-25g / l potassium borohydride and deionized water, the working temperature is 65-70°C, and the working time is 5-8min; (3) Metallization of the uncovered portion of the ceramic substrate surface: Immersing the ceramic substrate obtained in step (2) in a chemical copper plating solution for chemical plating, so that the surface is covered with a layer of copper metal layer to achieve the goal of metallization, and then taking it out for washing; wherein the specific composition of the chemical copper plating solution is 5 to 8 g / l Cu 2+ , 1-3 g / l aminosulfonic acid, 2-5 g / l aspartic acid, 15-25 g / l ethylenediaminetetraacetic acid, 10-25 g / l tartaric acid, 15-30 g / l reducing agent, 3-8 ppm surfactant, 2-5 ml / l ethylene glycol, 5-10 ppm stabilizer; Cu 2+ It is provided by one or more of copper acetate, copper sulfate, and copper oxalate, the reducing agent is one or two of glyoxylic acid and potassium borohydride, the surfactant is one or more of hexadecyltrimethylammonium bromide, dioctyl sodium sulfosuccinate, and taurine, the stabilizer is one or more of isothiourea propanesulfonic acid inner salt, urea, stannous sulfate, malic acid, and S-carboxyethyl isothiourea humid salt, and the solvent is deionized water; its working temperature is 85-90°C, the working time is 85-90min, and the pH is maintained at 8.5-9 during the working process; (4) Removing the 3D printing ink covering layer: Immersing the ceramic obtained in step (3) in an ethanol solution to dissolve the 3D printing ink covering layer, then taking it out, washing it with water and air-drying it, thereby obtaining a surface selectively metallized ceramic.

2. The surface selectively metallized ceramic according to claim 1, characterized in that: The ceramic substrate in step (1) includes an Al2O3 ceramic substrate, a BeO ceramic substrate or an AlN ceramic substrate.

3. The surface selectively metallized ceramic according to claim 1, characterized in that: During the working process of the degreasing solution in step (2) (a), the pH value is maintained at 7.5-8 with aqueous ammonia.

4. The surface selectively metallized ceramic according to claim 1, characterized in that: During the working process of the chemical copper plating solution in step (3), the pH value is maintained at 8.5-9 using 50 v / v% ammonia water and 20 wt% H2SO4, wherein the 50 v / v% ammonia water is obtained by mixing ammonia water and deionized water in a volume ratio of 1:

1.

5. The surface selectively metallized ceramic according to claim 1, characterized in that: The ethanol solution in step (4) is a 30-45 v / v % ethanol solution, the working temperature is 20-30° C., and the working time is 10-25 min.

6. A method for preparing a surface selectively metallized ceramic, characterized in that: Prepared by the following steps: (1) Ceramic substrate surface coverage: Using 3D printing ink to accurately cover the parts of the ceramic substrate surface that do not require metallization, and then let them dry naturally for later use; (2) Pretreatment of the uncovered portion of the ceramic substrate surface: The ceramic substrate obtained in step (1) is pretreated, and the specific operation is as follows: (a) Degreasing and surface hydroxylation: immersing the ceramic substrate obtained in step (1) in a degreasing solution to remove substances including oxides and grease on the surface of the ceramic substrate and forming a hydroxyl layer on the surface, and then taking it out for washing; wherein the degreasing solution specifically comprises 30-40 g / l ammonia water, 25-35 g / l Na2CO3, 15-30 g / l NaHCO3, 25-40 g / l NaH2PO4, 5-8 g / l Tween-60, 25-35 g / l Na2SiO3, 10-15 g / l H2O2, 0.3-0.8 g / l N-acetoacetanilide and deionized water, and the working temperature is 65-70°C, the working time is 5-10 min, and the pH is maintained at 7.5-8 during the working process; (b) Formation of a self-assembled monolayer and its densification: immersing the ceramic substrate obtained in step (a) in an ethanol solution containing a grafting agent to obtain a self-assembled monolayer on the ceramic substrate, then taking it out, washing it with water and drying it, and then baking it in an inert gas to densify the self-assembled monolayer; wherein the ethanol solution containing the grafting agent is an ethanol solution containing 10 to 25 g / l of silane coupling agent KH-550, its working temperature is 25 to 30°C, and the working time is 15 to 25 min; the drying temperature is 45 to 65°C, and the drying time is 5 to 10 min; the inert gas is N2 or Ar, the baking temperature is 55 to 65°C, and the baking time is 30 to 45 min; (c) Activation: The ceramic substrate with the self-assembled monolayer obtained in step (b) is immersed in a 2+ The activation solution is used to capture Ni 2+ After taking it out, immerse it in a reducing solvent to capture Ni 2+ It is reduced to Ni, and then taken out and washed for use; among them, Ni 2+ Provided by one or more of nickel acetate, nickel sulfate, nickel sulfamate, and basic nickel carbonate; containing Ni 2+ The specific composition of the activation solution is 15-25g / l Ni 2+ , 5-10g / l glycolic acid, 15-20g / l malic acid, 10-25g / l lactic acid and deionized water, the working temperature is 25-35°C, and the working time is 5-20min; the specific components of the reducing solvent are 15-25g / l potassium borohydride and deionized water, the working temperature is 65-70°C, and the working time is 5-8min; (3) Metallization of the uncovered portion of the ceramic substrate surface: Immersing the ceramic substrate obtained in step (2) in a chemical copper plating solution for chemical plating, so that the surface is covered with a layer of copper metal layer to achieve the goal of metallization, and then taking it out for washing; wherein the specific composition of the chemical copper plating solution is 5 to 8 g / l Cu 2+ , 1-3 g / l aminosulfonic acid, 2-5 g / l aspartic acid, 15-25 g / l ethylenediaminetetraacetic acid, 10-25 g / l tartaric acid, 15-30 g / l reducing agent, 3-8 ppm surfactant, 2-5 ml / l ethylene glycol, 5-10 ppm stabilizer; Cu 2+ It is provided by one or more of copper acetate, copper sulfate, and copper oxalate, the reducing agent is one or two of glyoxylic acid and potassium borohydride, the surfactant is one or more of hexadecyltrimethylammonium bromide, dioctyl sodium sulfosuccinate, and taurine, the stabilizer is one or more of isothiourea propanesulfonic acid inner salt, urea, stannous sulfate, malic acid, and S-carboxyethyl isothiourea humid salt, and the solvent is deionized water; its working temperature is 85-90°C, the working time is 85-90min, and the pH is maintained at 8.5-9 during the working process; (4) Removing the 3D printing ink covering layer: Immersing the ceramic obtained in step (3) in an ethanol solution to dissolve the 3D printing ink covering layer, then taking it out, washing it with water and air-drying it, thereby obtaining a surface selectively metallized ceramic.

7. The method for preparing a surface selectively metallized ceramic according to claim 6, characterized in that: The ceramic substrate in step (1) includes an Al2O3 ceramic substrate, a BeO ceramic substrate or an AlN ceramic substrate.

8. The method for preparing a surface selectively metallized ceramic according to claim 6, characterized in that: During the working process of the degreasing solution in step (2) (a), the pH value is maintained at 7.5-8 with aqueous ammonia.

9. The method for preparing a surface selectively metallized ceramic according to claim 6, characterized in that: During the working process of the chemical copper plating solution in step (3), the pH value is maintained at 8.5-9 using 50 v / v% ammonia water and 20 wt% H2SO4, wherein the 50 v / v% ammonia water is obtained by mixing ammonia water and deionized water in a volume ratio of 1:

1.

10. The method for preparing a surface selectively metallized ceramic according to claim 6, characterized in that: The ethanol solution in step (4) is a 30-45 v / v % ethanol solution, the working temperature is 20-30° C., and the working time is 10-25 min.

11. Use of the surface selectively metallized ceramic according to any one of claims 1 to 5 in electronic packaging.

Citation Information

Patent Citations

  • Ceramic surface metallization method and metallized ceramic

    CN114163259A

  • Method for improving binding force of electrocoppering on surface of ceramic substrate

    CN114990533A

  • Electroless copper plating solution composition and electroless copper plating method using same

    CN105593403A

  • Self-assembled patterned ceramic substrate for chemical copper plating and preparation method and application thereof

    CN115119393A

  • Activation method for chemical plating of non-metallic material and chemical plating therefor

    CN1966765A